2012
DOI: 10.1182/blood-2012-01-404681
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal B-cell lymphocytosis: right track or red herring?

Abstract: Monoclonal B-cell lymphocytosis (MBL), a newly recognized entity found in approximately 3% of normal persons, precedes chronic lymphocytic leukemia. However, MBLs progress into overt malignancy only in a very minor portion of cases, thus raising the clinical concern of whether and how we can discriminate at diagnosis which rare cases will evolve into a fully fledged tumor. Understanding the molecular/ biologic features underlying the risk of progression may significantly modify our strategies for correctly man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 65 publications
(78 reference statements)
5
44
0
Order By: Relevance
“…Chronic lymphocytic leukemia-type MBL has a rate of progression to CLL of only 1-2%/year. [35][36][37][38] However, almost all CLL are preceded by MBL. 7 The situation may be similar with MCLBUS, although the proportion of MCL with preceding in situ MCL or small foci of cyclin D1 + lymphoid cells is controversial.…”
Section: Kappa Bcl2mentioning
confidence: 99%
“…Chronic lymphocytic leukemia-type MBL has a rate of progression to CLL of only 1-2%/year. [35][36][37][38] However, almost all CLL are preceded by MBL. 7 The situation may be similar with MCLBUS, although the proportion of MCL with preceding in situ MCL or small foci of cyclin D1 + lymphoid cells is controversial.…”
Section: Kappa Bcl2mentioning
confidence: 99%
“…7 A correlation between platelet count and age was also found by a larger study that evaluated 12,142 adult inhabitants of the United States and found statistically significant differences between young and old individuals. 8 However, these differences were small: less than 30x10 9 /L between people of 17-19 years and those over 70. Thus, until a few years ago, both the existence and the possible extent of age-related changes in platelet count were uncertain, but a series of cross-sectional studies performed recently in different Italian populations has definitively clarified this matter.…”
Section: Platelet Count and Agingmentioning
confidence: 99%
“…6 In contrast, a progressive decline in platelet count with aging was shown a few years later in 477 ambulatory patients, with a difference of over 100x10 9 /L between children aged 1-5 years old and seniors over the age of 71 years. 7 A correlation between platelet count and age was also found by a larger study that evaluated 12,142 adult inhabitants of the United States and found statistically significant differences between young and old individuals.…”
Section: Platelet Count and Agingmentioning
confidence: 99%
See 2 more Smart Citations